The Ashgate research companion to Experimental Music - Saunders, James (Farnham Ashgate, 2009)
The recent resurgence of experimental music has given rise to a more divergent range of practices than has previously been the case. The Ashgate Research Companion to Experimental Music reflects these recent developments by providing examples of current thinking and presenting detailed case studies that document the work of contemporary figures. The book examines fourteen current practitioners by interrogating their artistic practices through annotated interviews, contextualized by nine authored chapters which explore central issues that emerge from and inform these discussions. Whilst focusing on composition, the book also encompasses related aspects of performance, improvisation and sonic art. The interviews all explore how the selected artists work, focusing on the processes involved in developing their recent projects, set against more general aesthetic concerns. They aim to shed light on the disparate nature of current work whilst seeking to find possible points of contact. Many of the practitioners are active in areas that span disciplines, such as composition and improvisation, and the book explores the interaction of these activities in the context of their work. The other chapters consider a range of issues pertinent to recent developments in the genre, including: definitions of experimentalism and its relationship with a broader avant garde; experimentalism and cultural change; notation and its effect on composition; realising open scores; issues of notation and interpretation in live electronic music; performing experimental music; improvisation and technology; improvisation and social meaning; instrumentalizing objects; visual artists' relationships to experimental music; working across interdisciplinary boundaries; listening and the soundscape; working methods, techniques and aesthetics of recent experimental music.